2020
DOI: 10.1245/s10434-019-08192-z
|View full text |Cite
|
Sign up to set email alerts
|

ALPPS for Locally Advanced Intrahepatic Cholangiocarcinoma: Did Aggressive Surgery Lead to the Oncological Benefit? An International Multi-center Study

Abstract: Background. ALPPS is found to increase the resectability of primary and secondary liver malignancy at the advanced stage. The aim of the study was to verify the surgical and oncological outcome of ALPPS for intrahepatic cholangiocarcinoma (ICC). Methods. The study cohort was based on the ALPPS registry with patients from 31 international centers between August 2009 and January 2018. Propensity score matched patients receiving chemotherapy only were selected from the SEER database as controls for the survival a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 51 publications
(58 reference statements)
1
53
0
3
Order By: Relevance
“…Completion of the resection is performed at a second operation once sufficient FLR hypertrophy is confirmed with volumetry, typically 1–2 weeks later [ 76 ]. An international multi-institutional study of ALPPS included 102 patients with ICC; despite high 90-day mortality, ALPPS was associated with high rates of achieving R0 resection (N = 87, 85%) in locally advanced ICC with improved OS compared with palliative chemotherapy alone (median OS: 26.4 months versus 14 months; 1-, 2-, and 3-year survival: 82.4%, 70.5%, and 39.6% versus 51.2%, 21.4%, and 11.3%, respectively, p < 0.01 [ 77 ]. Nevertheless, the use of ALPPS remains controversial given its relatively high morbidity and mortality and should be limited to high-volume experienced institutions [ 76 ].…”
Section: Surgical Principlesmentioning
confidence: 99%
“…Completion of the resection is performed at a second operation once sufficient FLR hypertrophy is confirmed with volumetry, typically 1–2 weeks later [ 76 ]. An international multi-institutional study of ALPPS included 102 patients with ICC; despite high 90-day mortality, ALPPS was associated with high rates of achieving R0 resection (N = 87, 85%) in locally advanced ICC with improved OS compared with palliative chemotherapy alone (median OS: 26.4 months versus 14 months; 1-, 2-, and 3-year survival: 82.4%, 70.5%, and 39.6% versus 51.2%, 21.4%, and 11.3%, respectively, p < 0.01 [ 77 ]. Nevertheless, the use of ALPPS remains controversial given its relatively high morbidity and mortality and should be limited to high-volume experienced institutions [ 76 ].…”
Section: Surgical Principlesmentioning
confidence: 99%
“…In patients with insufficient FLRV, some authors have proposed associating liver partition and portal vein ligation for staged hepatectomy (ALPPS) in order to induce significant hypertrophy in a short time. An Italian multicenter study [59] conducted on CCA patients (either pCCA or iCCA) subjected to ALPPS, showed worse cumulative morbidity and mortality, and these findings have been confirmed in a recent case-control study conducted in the ALPPS International Registry [60] . In light of the high postoperative mortality (40-44%), ALPPS is no longer considered in patients with pCCA, and portal embolization remains the procedure of choice in order to increase residual liver volume in patients who are candidates for major or extended hepatectomies; ALPPS should be considred for selected cases of iCCA.…”
Section: Surgerymentioning
confidence: 66%
“…Ninety-nine completed the second stage, with a median interstage duration of 11 days, showing high efficacy in achieving R0 resections in locally-advanced iCCA (87 patients, 85%). The benefit of ALPPS on OS was confirmed in iCCA patients with a centrally-located single lesion, but not in patients with multiple lesions when compared with only chemotherapy [60] . A modified version of the ALPPS technique, tourniquet-ALPPS, has recently been evaluated in a case series, where it was found to have a better mortality rate with respect to the traditional technique, though this requires further evaluation [61] .…”
Section: Surgerymentioning
confidence: 88%
“…In the registry cohort study from 31 international institutes, 102 patients with locally advanced ICC undergoing ALPPS were recruited. 6 The R0 resection rate was 85%. The initial high morbidity and mortality rates decreased steadily to a 29% severe complication rate and 7% 90-day mortality in the last 2 years.…”
Section: Presentmentioning
confidence: 97%